Impacto da otimização de funções hash no desempenho do algoritmo de assinatura digital pós-quântica CRYSTALS-Dilithium - Meneses, Rodrigo Duarte de; Henriques, Marco Aurélio Amaral (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.234084, 2023)
The CRYSTALS-Dilithium digital signature algorithm is one of the post-quantum algorithms recently standardized by NIST. From studies in the literature indicating a computational overhead associated with the hash functions used in the algorithm, we optimized its implementation with the adoption of the TurboSHAKE hash function. Such optimization conferred a higher speed to Dilithium at all levels of security, without changing the use of RAM.